Faulty antenna detection in a linear array using simulated annealing optimization - Boopalan N.; Ramasamy A.K.; Nagi F.H. (Institute of Advanced Engineering and Science, 2023)
Sonar, radar and communication systems solely depend on antenna arrays for signal attainment. These arrays are capable of producing directional signals which can be steered in a certain direction. Faulty elements in an array will result in distorted radiation pattern with increased sidelobe levels. Far-field faulty antenna detection is necessary due to the near field repairing at complex systems like spacecraft. This paper proposes simulated annealing (SA) optimizing method to find the faulty element's location in a linear array. In this study, a Chebyshev array is presented with the SA optimization method to detect faulty element location with a random permutation of failure locations tested. This method can successfully detect faulty antenna in a linear array. Even though, this method is developed for linear array it can easily be adapted to a planar array. 2020 Institute of Advanced Engineering and Science. All rights reserved.